Acute isoniazid neurotoxicity in childhood - Çıtak, Agop; Kaya, Özlen; Üçsel, Raif; Karaböcüoğlu, Metin; Uzel, Nedret (The Turkish Journal of Pediatrics, 2002)
Acute isoniazid (INH) poisoning is uncommon in children. Although most physicians are aware of INH hepatotoxicity, acute INH poisoning and its treatment are not well recognized. INH is increasingly being used to control the spread of tuberculosis, and physicians should know its potentially fatal effects. INH overdose is known to result in rapid onset of seizures, metabolic acidosis and prolonged obtundation. We report two cases of obtundation secondary to INH overdose that was immediately reversed by pyridoxine. Parenteral pyridoxine administration is an effective method in INH intoxication. The intravenous form of pyridoxine must be available in the emergency care units, and INH toxicity should be suspected in any patient with refractory seizures and metabolic acidosis.